(untitled) (Revista de Artes Marciales Asiáticas, 2021)
Penalties in judo result from negative actions that are not in line with judo combat regulations. The aim of the research was to determine the differences in penalties between winner and non-winner competitors in judo. A total of 1799 (men=1133 and women=666) matches with penalties were evaluated during 2017, 2018 and 2019 World Judo Championships. The variables were expressed as proportions and compared with the Chi-Square test with pairwise Z-tests. The ratio of receiving the first and second shido was the same in men and women athletes (p>.05), but it was different for weight categories (p<.05). The ratio of shido penalty was different between winner and non-winner athletes, the ratio of the second shido was lower in winner athletes (p<.05). While the ratio of forbidden action was the same in winner and non-winner athletes (p>.05), the ratio of forbidden actions in the first and second shido differed (p<.05). The difference in the penalty ratios in winner and non-winner athletes, especially the difference in forbidden actions leading to first and second shido may reflect some tactical differences. The results of this research can significantly contribute to the understanding of the significance of judo penalties both in training and in competition, as well as to the further study of judo penalties.